(untitled) (Revista de História da UEG (REVHIST), 2021)
The presence of conspiracy theories in Olavo de Carvalho’s thought, considered the guru of the new Brazilian rights, is cause for curiosity and jokes. The mobilization of irrationalities and the production of powerful and invisible enemies permeate the thought of the self-entitled philosopher, a direct ancestor of Bolsonarism. Carvalho has a clear influence on the government of Jair Bolsonaro, appointing ministries and having students from his online courses in important positions in Legislative and Executive branches. Therefore, the intention of this article is to analyze and reflect on some of the main exponents of bolsolavismo: cultural Marxism and globalism. These ideas permeate the federal government, both in the statements of the president and parliamentarians of its allied base, as well as in the construction of political projects and transferring of public funds to certain areas. Additionally, in the scenario of the covid-19 pandemic, the conspiracy also has a clear influence, mainly on the idea of ​​early treatment and the anti-vaccine movement, both stimulated by the president. This article hopes to contribute to the elaboration of hypotheses so that the current scenario of political and health crisis is better analyzed. Keywords: Conspiracy. Olavo de Carvalho. Jair Bolsonaro. Cultural Marxism. Globalism. Pandemic.